Mental Anorexia In A Teenager. A Case Report - Smaranda Diaconescu; Anamaria Ciubara; Nicoleta Gimiga; Amalia Constantin; Claudia Olaru (Romanian Society of Oral Rehabilitation, 2013)
Anorexia nervosa is an eating disorder observed with increasing frequency, especially among adolescent females. No consensus exists concerning the causes of the disorder. Social, psychosexual, family emotional climate, biological theories, and a "regression hypothesis" (Crisp, 1986) have been advanced to explain the phenomenon. The major characteristics of the disease are 25% loss of body weight, use of various means to lose weight, weight phobia, preoccupation with food, body image disturbances, as well as numerous associated medical conditions: bradycardia, hypotension, dehydration, hypothermia, electrolyte abnormalities, amenorrhoea, metabolic changes, and abdominal distress. We present the case of a teenager girl aged 15, hospitalized in our clinic for investigations, presenting weight loss (11 kg in 3 months). Clinical examination on admission revealed paleness, fat loss, muscle atrophy, diminished tendon reflexes, bradycardia, epigastric pain and secondary amenorrhoea. An initial suspicion of abdominal tumour was invalidated by abdominal CT. Electrolyte disturbances, hypercholesterolemia, low levels of FSH and LH and prolactin in normal ranges, increased urinary and blood amylase in association with normal hypothalamic MRI and neuropsychiatric examination established the diagnosis. A favourable evolution was noticed after treatment with antidepressants and anxiolytics in association with a refuelling program and psychotherapy, resulting in weight gain and reappearance of menses.